2010
DOI: 10.1080/10401334.2010.488460
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Evidence Based Medicine Into Undergraduate Medical Education: Combining Online Instruction With Clinical Clerkships

Abstract: Medical students successfully acquired and independently applied EBM skills following extended, online, faculty mentored instruction. This method of instruction provided uniform instruction across geographic sites and medical specialties and permitted efficient use of faculty time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 13 publications
3
83
1
1
Order By: Relevance
“…2 Many different strategies have been used for teaching EBDM including lectures, discussion groups, journal clubs, and responding to questions generated during clinical practice experiences. [3][4][5][6][7][8][9] Different outcome measures (knowledge, attitudes and skills) have been used to assess EBDM competence. 10 Some of these measures include: self-report of skills, 11 use of tools to evaluate critical appraisal skills, 4,5 use of validated tools (eg, Fresno and Berlin assessment tool) to assess EBDM skills and knowledge, 5,6 and structured evaluation of answers to actual practice-based clinical questions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Many different strategies have been used for teaching EBDM including lectures, discussion groups, journal clubs, and responding to questions generated during clinical practice experiences. [3][4][5][6][7][8][9] Different outcome measures (knowledge, attitudes and skills) have been used to assess EBDM competence. 10 Some of these measures include: self-report of skills, 11 use of tools to evaluate critical appraisal skills, 4,5 use of validated tools (eg, Fresno and Berlin assessment tool) to assess EBDM skills and knowledge, 5,6 and structured evaluation of answers to actual practice-based clinical questions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Some of these measures include: self-report of skills, 11 use of tools to evaluate critical appraisal skills, 4,5 use of validated tools (eg, Fresno and Berlin assessment tool) to assess EBDM skills and knowledge, 5,6 and structured evaluation of answers to actual practice-based clinical questions. [5][6][7][8][9] The University of Wisconsin-Madison School of Pharmacy teaches a semester-long course in drug literature evaluation that focuses on reading and critical appraisal of primary research literature. To expand students' ability in EBDM, a longitudinal education program that includes training regarding searching for, interpreting, and applying information from secondary sources of literature (systematic reviews/meta-analyses) was designed.…”
Section: Introductionmentioning
confidence: 99%
“…Student self-assessment typically revealed positive attitudes toward online lectures as a teaching modality [7,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32]. Finally, multiple studies demonstrated that knowledge was equivalent (or better) between students learning through online lectures compared to traditional learning modalities, such as live didactic lectures [8,9,12,19,22,23,25,28,[33][34][35][36]…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%
“…EBM components were introduced into preclinical years in various ways: offered as a short EBM course of eight contact hours enhanced with problem based learning small group discussion sessions facilitated by clinicians (Srinivasan et al, 2002); integrated into courses such as Library Science and Medical Informatics, Epidemiology, Microbiology (Barnett et al, 2000), and Mastering Medical Information (Holloway et al, 2004); taught as part of a series of educational interventions in an elective family medicine preceptorship program for first and second-year medical students (Nieman, Cheng, & Foxhall, 2009); and offered as a course of 22 contact hours at the end of Year 1 (West et al, 2011). In clinical years, EBM was integrated with clinical educational experiences through inpatient and outpatient primary care clerkship rotations of internal medicine, family medicine, and several other core clinical clerkships (Aronoff et al, 2010;Cayley, 2005;Dorsch et al, 2004;Ghali et al, 2000;Sastre et al, 2011;Schilling et al, 2006;Thomas & Cofrancesco, 2001;Wadland et al, 1999). Among the 13 studies, only two studies, one by Barnett et al (2000) and the other by West et al (2011), had a longitudinal EBM curriculum that spanned the preclinical curriculum and clinical core clerkships.…”
Section: Design and Development Of Ebm Interventionsmentioning
confidence: 99%
“…Barnett et al (2000) evaluated EBM instruction integrated into the first-year medical education curriculum and clinical education; while the study by West et al (2011) reported the outcomes of a longitudinal EBM into the second-year preclinical education and third-year core clinical rotations. Studies on EBM during clinical rotations were conducted at various settings of clerkships of internal medicine, family medicine, and pediatrics on community campuses (Wadland et al, 1999), outpatient internal medicine clerkship (Ghali et al, 2000;Thomas & Cofrancesco, 2001), inpatient portion of internal medicine clerkship blocks (Sastre et al, 2011), family medicine clerkship (Cayley, 2005;Schilling et al, 2006), or core clinical clerkship rotations such as internal medicine, surgery, pediatrics, obstetrics and gynecology, neurology, and psychiatry (Aronoff et al, 2010;Barnett et al, 2000;West et al, 2011).…”
Section: Description Of Studiesmentioning
confidence: 99%